Analisis Standar Operasional Prosedur Proses Produksi Pupuk Dolomit di PT. Magnesium Gosari Internasionl - Maulidah, Ananda Wahyu; Agustina, Rohmatin; Anggun, Arini Roro (Jurnal Ekonomi Pertanian dan Agribisnis, 2025)
Standard Operating Procedures (SOP) play a crucial role in ensuring quality and consistency in the dolomite fertilizer production process. This study aims to analyze the implementation of SOP in the production process at PT. Magnesium Gosari Internasional. Using a qualitative activies, interviews with production managers and staff, and a review of relevant literature. The findings reveal that the company’s SOP implementation effectively enchances work efficiency, product quality consistency, and workplace safety while minimizing errors, SOP also ensure compliance with industry standards, support controlled operations, and improve the companys’s sompetitiveness. The effectiveness of SOP in maintaining operational stability demonstrates the company’s ability to meet market demands and foster trust with customers and business partners. By implementing well-structured SOP PT. Magnesium Gosari Internasional successfully strengthens its market position and sustainability in the fertilizer industry.